THE PROBLEM OF THE GENERAL SOLUTION OF ANALYSIS AND PROBLEMS SYNTHESIS IN LINEAR CONTROL SYSTEMS - Kirichenko , N. F.; Krivonos , Yu. G.; Krak , Yu. V. (Problems of Informatization and Management, 2021)
On the basis of the broken-down method of drilling pseudo-blending matrices [1], the problems of understanding the outward solution of problems of analysis and synthesis in linear discrete keruvanny systems are considered. We look at the tasks of termial keruvannya and caution, identification, the synthesis of matrices in systems with caution, the synthesis of linear conversions in systems with a discrete argument.